2012
DOI: 10.1103/physreve.86.016323
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization and free decay in surface quasigeostrophic flows

Abstract: We derive statistical equilibrium solutions of the truncated inviscid surface quasigeostrophic (SQG) equations, and verify the validity of these solutions at late times in numerical simulations. The results indicate the pseudoenstrophy thermalizes while the pseudoenergy can condense at the gravest modes, in agreement with previous indications of a direct cascade of pseudoenstrophy and an inverse cascade of pseudoenergy in forced-dissipative SQG systems. At early times, the truncated inviscid SQG simulations sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The evolution to statistical equilibria can also be examined in terms of spectral properties. In this context, Teitelbaum and Mininni [57] showed that generalized enstrophy thermalizes (the spectra of buoyancy variance behaving as k for large k), while generalized energy condenses (piling up at the largest scale).…”
Section: Physical Properties Of the Cascadementioning
confidence: 99%
“…The evolution to statistical equilibria can also be examined in terms of spectral properties. In this context, Teitelbaum and Mininni [57] showed that generalized enstrophy thermalizes (the spectra of buoyancy variance behaving as k for large k), while generalized energy condenses (piling up at the largest scale).…”
Section: Physical Properties Of the Cascadementioning
confidence: 99%
“…In the simulations, energy was initially concentrated at low wave numbers and was let to cascade to larger ones, and a long transient following the previous description was observed before the system reached full thermalization. The results were extended to helical hydrodynamic flows [6], magnetohydrodynamics [7], compressible flows [8], quantum turbulence [9,10], gyrokinetic plasma systems [11], the dyamo problem [12,13], and also to study the decay of quasigeostrophic turbulence [14].…”
Section: Introductionmentioning
confidence: 99%